Analysis of Heparins Derived From Bovine Tissues and Comparison to Porcine Intestinal Heparins. (September 2016) - St Ange, Kalib; Onishi, Akihiro; Fu, Li; Sun, Xiaojun; Lin, Lei; Mori, Daisuke; Zhang, Fuming; Dordick, Jonathan S.; Fareed, Jawed; Hoppensteadt, Debra; Jeske, Walter; Linhardt, Robert J.
Heparin is a widely used clinical anticoagulant. It is also a linear glycosaminoglycan with an average mass between 10 and 20 kDa and is primarily made up of trisulfated disaccharides comprised of 1, 4-linked iduronic acid and glucosamine residues containing some glucuronic acid residues. Heparin is biosynthesized in the Golgi of mast cells commonly found in the liver, intestines, and lungs. Pharmaceutical heparin currently used in the United States is primarily extracted from porcine intestines. Other sources of heparin including bovine intestine and bovine lung are being examined as potential substitutes for porcine intestinal heparin. These additional sources are intended to serve to diversify the heparin supply, making this lifesaving drug more secure. The current study examines bovine heparins prepared from both intestines and lung and compares these to porcine intestinal heparin. The structural properties of these heparins are examined using nuclear magnetic resonance, gel permeation chromatography, and disaccharide analysis of heparinase-catalyzed depolymerized heparin. The in vitro functional activities of these heparins have also been determined. The goal of this study is to establish the structural and functional similarities and potential differences between bovine and porcine heparins. Porcine and bovine heparins have structural and compositional similarities and differences.